Self-adhesive adhesive composition and self-adhesive product
A chloroprene rubber latex-based adhesive composition with controlled melting endotherm and crystallinity, using a specific tackifier resin, addresses the issue of self-adhesive strength degradation by suppressing crystallization, ensuring long-term adhesion stability.
Patent Information
- Application Number
- JP2023166190
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing self-adhesive adhesives face issues with a decrease in self-adhesive strength over time, particularly in chloroprene rubber latex-based compositions, due to crystallization of the latex rubber elastomer component.
A self-adhesive pressure-sensitive adhesive composition containing chloroprene rubber latex with controlled melting endotherm and crystallinity, achieved by using a specific ratio of tackifier resin such as an aromatic modified terpene resin and rosin ester resin, to suppress crystallization and maintain self-adhesive strength stability.
The composition ensures excellent stability of self-adhesive strength over time at room temperature, accelerated conditions, and low temperatures, providing self-adhesive products with consistent adhesion properties.
Smart Images

Figure 2025056609000001 
Figure 2025056609000002 
Figure 2025056609000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a self-adhesive adhesive composition and a self-adhesive product having a self-adhesive adhesive layer formed from the composition. [Background technology]
[0002] Currently, self-adhesive adhesives containing natural rubber latex-based adhesives are widely used for medical self-adhesive tapes such as self-adhesive bandages (see, for example, Patent Document 1 and Patent Document 2). Generally, self-adhesive adhesives are required to have little tack (stickiness), to adhere strongly to surfaces coated with the adhesive, and to be fixed so as not to peel off easily, and the above-mentioned natural rubber latex-based adhesives have been used as self-adhesive adhesives that can satisfy these performance requirements. However, from the viewpoint of the risk of latex allergies in medical settings, there is an increasing demand for self-adhesive adhesives for such applications to be free of natural rubber latex.
[0003] In response to the above-mentioned trend away from natural rubber latex, for example, a self-adhesive adhesive composition and a self-adhesive product have been proposed that employ chloroprene rubber latex as the elastomer component of the self-adhesive adhesive, achieving both low tack and high self-adhesion (Patent Document 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 63-260553 [Patent Document 2] Japanese Patent Application Publication No. 11-89874 [Patent Document 3] JP 2022-168718 A Summary of the Invention [Problem to be solved by the invention]
[0005] As mentioned above, various proposals and studies have been made on self-adhesive pressure sensitive adhesives from the viewpoints of eliminating natural rubber latex and improving tackiness and self-adhesiveness. An object of the present invention is to provide a novel self-adhesive pressure-sensitive adhesive composition and a self-adhesive product based on the new viewpoint that there is little change (decrease) in the self-adhesive strength over time. [Means for solving the problem]
[0006] That is, the present invention relates to the following self-adhesive pressure-sensitive adhesive composition and self-adhesive product. [1] A self-adhesive pressure-sensitive adhesive composition containing latex rubber as an elastomer component, the self-adhesive pressure-sensitive adhesive composition satisfying at least one of the following (1) and (2): (1) After storage for one month in an environment at 23°C, the self-adhesive pressure-sensitive adhesive composition has a melting endotherm of 0.5 J / g or less, as measured with a differential scanning calorimeter (DSC) (heating and cooling conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, measurement temperature range: 0°C to 80°C, in a nitrogen atmosphere). (2) After storage for one month in an environment at 5°C, the self-adhesive pressure-sensitive adhesive composition has a melting endotherm of 0.1 J / g or less, as measured with a differential scanning calorimeter (DSC) (heating and cooling conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, measurement temperature range: 0°C to 80°C, in a nitrogen atmosphere). [2] The self-adhesive pressure-sensitive adhesive composition according to [1], which further satisfies at least one of the following (3) and (4): (3) After storage for one month in an environment at 23° C., the self-adhesive pressure-sensitive adhesive composition has a degree of crystallinity of 15% or less as measured by DSC. (4) After storage for one month in an environment at 5°C, the self-adhesive pressure-sensitive adhesive composition has a crystallinity of 5% or less as determined by DSC measurement. [3] The self-adhesive adhesive composition according to [1], wherein the self-adhesive adhesive composition contains a tackifier resin, and the tackifier resin is a mixed resin of an aromatic modified terpene resin and a rosin ester resin, or a terpene phenol resin. [4] The self-adhesive adhesive composition according to [3], wherein the latex rubber is a chloroprene rubber latex, and the tackifier resin is contained in a ratio of 45 to 80 parts by mass per 100 parts by mass of the chloroprene rubber latex, calculated as a solid content. [5] A self-adhesive product having a substrate and a self-adhesive layer formed on at least one surface of the substrate from the self-adhesive adhesive composition according to any one of [1] to [4]. Effect of the Invention
[0007] The self-adhesive adhesive composition of the present invention can be made to have excellent stability of self-adhesive strength over time at room temperature (23°C), under accelerated conditions (40°C, 75% RH), and at low temperatures (5°C). Therefore, by using the self-adhesive adhesive composition of the present invention, it is possible to provide self-adhesive products such as adhesive dressings and bandages which have excellent stability of self-adhesive power over time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The "self-adhesive" of the self-adhesive adhesive composition and self-adhesive product of the present invention refers to an adhesive that is itself slightly tacky (has an initial tackiness) and exhibits adhesion between adhesives even under relatively weak pressure, but shows little adhesion to many other substances even when strong pressure is applied. For example, in a self-adhesive product having adhesive layers (adhesive surfaces) formed from the self-adhesive adhesive composition on both sides of a substrate, the adhesive layers (adhesive surfaces) adhere to each other, allowing the product to be wound straight, and the product can be unwound with a relatively light force during use (the force required to unwind from a roll under specified conditions is small, i.e., tape, etc. is easy to unwind), and the adhesive layers exhibit adhesion even under relatively weak pressure, resulting in good fixing function.
[0009] The present inventors have noticed that, in the self-adhesive pressure-sensitive adhesive compositions proposed thus far, even if they initially have low tackiness and high self-adhesion, the self-adhesion may decrease over time. The researchers then investigated the causes of the decrease in self-adhesive strength, and concluded that one of the causes is the crystallization of the latex rubber, which is an elastomer component, and that suppressing this crystallization would lead to improved stability of the self-adhesive strength over time. On the other hand, they focused on the thermal history of crystalline substances measured by differential scanning calorimetry, and in particular on the amount of melting endotherm, which is thought to be correlated with the proportion of crystalline matter. Then, by focusing on the amount of heat of melting of the self-adhesive pressure-sensitive adhesive composition as an index of crystallization of the latex rubber, it was discovered for the first time that when the amount of heat of melting of the self-adhesive pressure-sensitive adhesive composition after a predetermined period of time is maintained at or below a predetermined value, the decrease in the self-adhesive strength of the self-adhesive pressure-sensitive adhesive composition is suppressed, that is, there is a correlation between the suppression of crystallization of the latex rubber and the suppression of the decrease in self-adhesive strength. Furthermore, the inventors further investigated the composition of a self-adhesive adhesive composition that satisfies the above-mentioned specified heat of melting endotherm, i.e., that can suppress crystallization, and discovered that by selecting a tackifier resin that is highly compatible with latex rubber and by increasing the proportion of the tackifier resin in the composition, it is possible to suppress the crystallization of latex rubber, thereby completing the present invention. The present invention will be described in detail below.
[0010] <Self-adhesive adhesive composition> The self-adhesive adhesive composition of the present invention contains latex rubber as an elastomer component. and is characterized in that the melting endotherm after storage for a specified period of time is equal to or less than a specified value, as described below.
[0011] <Self-adhesive adhesive composition: melting endotherm> As mentioned above, in crystalline substances, there is a correlation between the proportion of crystalline matter and the amount of heat of fusion. In the thermal history measured by a differential scanning calorimeter (DSC), the peak temperature of fusion reflects the quality of the crystals, and the heat of fusion reflects the amount of crystals. In other words, the larger the amount of heat of fusion, the greater the amount of crystalline matter (crystallization) in the measurement target. The inventors performed differential scanning calorimetry (DSC) measurements on the subject self-adhesive adhesive composition under specified conditions after storing the composition for a specified period, and found a correlation between the melting endotherm value obtained by the measurements and the self-adhesive strength after storage for a specified period. The self-adhesive adhesive composition of the present invention is characterized in that it has the following melting endotherm under at least one of the following conditions: (1) storage for one month in an environment at a temperature of 23°C, and (2) storage for one month in an environment at a temperature of 5°C. (1) After storage for one month in an environment at 23°C, the self-adhesive pressure-sensitive adhesive composition has a melting endotherm of 0.5 J / g or less, as measured with a differential scanning calorimeter (DSC) (heating and cooling conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, measurement temperature range: 0°C to 80°C, in a nitrogen atmosphere). (2) After storage for one month in an environment at 5°C, the self-adhesive pressure-sensitive adhesive composition has a melting endotherm of 0.1 J / g or less, as measured with a differential scanning calorimeter (DSC) (heating and cooling conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, measurement temperature range: 0°C to 80°C, in a nitrogen atmosphere).
[0012] Self-adhesive pressure-sensitive adhesive composition: crystallinity In addition, the self-adhesive adhesive composition of the present invention can also be characterized by the degree of crystallinity after storage for a specified period of time, from the viewpoint that the amount of heat of fusion endotherm is equal to or less than a specified value after storage for a specified period of time, i.e., crystallization is suppressed, as described above. That is, the self-adhesive pressure-sensitive adhesive composition of the present invention can have a crystallinity that satisfies either or both of the following (3) and (4). (3) After storage for one month in an environment at 23° C., the self-adhesive pressure-sensitive adhesive composition has a degree of crystallinity of 15% or less as measured by DSC. (4) After storage for one month in an environment at 5°C, the self-adhesive pressure-sensitive adhesive composition has a crystallinity of 5% or less as determined by DSC measurement. In the present invention, the crystallinity (%) is expressed as the ratio of the value of the endothermic heat of fusion of the subject self-adhesive pressure-sensitive adhesive composition to the value of the endothermic heat of fusion obtained by performing differential scanning calorimetry (DSC) measurement on only the latex rubber (not including other components such as a tackifier resin described below), which is set to 100%.
[0013] Each component constituting the self-adhesive pressure-sensitive adhesive composition according to the present invention will be described in detail below. The self-adhesive pressure-sensitive adhesive composition according to the present invention essentially contains latex rubber as an elastomer component. Among the latex rubbers, chloroprene rubber latex can be preferably used in the present invention.
[0014] Chloroprene rubber latex (also called "chloroprene polymer latex") is a latex (emulsion) obtained by dispersing polychloroprene in water. Chloroprene rubber is a homopolymer of 2-chloro-1,3-butadiene (hereinafter referred to as chloroprene) or a copolymer of chloroprene and a monomer copolymerizable with chloroprene. Therefore, the chloroprene rubber latex may be (a) a latex obtained by dispersing a chloroprene homopolymer in water (hereinafter, also referred to simply as (a) chloroprene rubber latex), or (b) a copolymer of chloroprene and a copolymerizable monomer in water. Examples of the latex obtained by dispersing chloroprene rubber include (b) chloroprene rubber latex.
[0015] In the present invention, these (a) chloroprene rubber latex and (b) chloroprene rubber latex can be used alone or in combination. In the self-adhesive application of the present invention, it is preferable to use the above two types of chloroprene rubber latexes (a) and (b) in combination, from the viewpoint of easily achieving both an initial low tackiness (less sticky) and fixation by self-adhesion. For example, (a) chloroprene rubber latex and (b) chloroprene rubber latex may be blended in a mass ratio of (a):(b)=90:10 to 30:70, or alternatively, in a mass ratio of 90:10 to 50:50, calculated on a solid content basis.
[0016] Examples of the latex obtained by dispersing the (b) copolymer of chloroprene and a copolymerizable monomer in water include a copolymer of chloroprene and, for example, a carboxyl group-containing vinyl monomer (ethylenically unsaturated carboxylic acid), and a latex obtained by dispersing a copolymer of chloroprene, the carboxyl group-containing vinyl monomer, and further another vinyl monomer in water. Examples of the carboxyl group-containing vinyl monomer (ethylenically unsaturated carboxylic acid) include acrylic acid, methacrylic acid, crotonic acid, fumaric acid, maleic acid, maleic anhydride, citraconic acid, glutaconic acid, etc. Examples of the other vinyl monomers include ethylene, 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, butadiene, isoprene, styrene, esters such as methyl (meth)acrylate, (meth)acrylonitrile, etc. For example, (b) chloroprene rubber latex can be a latex obtained by dispersing a copolymer of chloroprene and methacrylic acid in water.
[0017] The above (a) chloroprene rubber latex and (b) chloroprene rubber latex can be obtained by emulsion polymerizing the above chloroprene alone or by emulsion polymerizing the above chloroprene and a carboxyl group-containing vinyl monomer or the like in the presence of an emulsifier, for example a rosin acid-based emulsifier such as rosin acid or a rosin acid metal salt.
[0018] Chloroprene rubber latex is characterized, for example, by the gel content (content of toluene-insoluble components) in the latex and the crystallization rate of the chloroprene homopolymer or chloroprene copolymer contained in the latex.
[0019] The gel content (content of toluene-insoluble components) of the above (a) chloroprene rubber latex and (b) chloroprene rubber latex usable in the present invention is not particularly limited as long as it does not impair the effects of the present invention. For example, the gel content may be in the range of about 0 to 20% by mass. The gel content of the chloroprene rubber latex can be measured, for example, by the following method. First, the chloroprene rubber latex is freeze-dried to obtain an aggregate. The obtained aggregate is immersed in toluene for 2 days and passed through a 200 mesh (opening 0.075 mm), and the material remaining on the mesh is vacuum-dried to remove the toluene and obtain a gel. The gel content can be calculated from the ratio of the weight of the gel to the weight of the aggregate.
[0020] The crystallization rates of (a) the chloroprene polymer in the chloroprene rubber latex and (b) the chloroprene copolymer in the chloroprene rubber latex usable in the present invention are not particularly limited as long as they do not impair the effects of the present invention. For example, when the above (a) and (b) are used in combination in the application of the self-adhesive property according to the present invention, (a) the chloroprene polymer in the chloroprene rubber latex is a type having a medium crystallization rate. (b) chloroprene rubber latex can be used in combination with a chloroprene copolymer with a medium to slow crystallization rate. Note that if a latex with a fast crystallization rate is used as the (b) chloroprene rubber latex, care should be taken when using it as it may not show self-adhesiveness.
[0021] As the above (a) chloroprene rubber latex and (b) chloroprene rubber latex, commercially available products can be used. Examples of commercially available chloroprene rubber latexes include the Showpren (registered trademark) series manufactured by Showa Denko K.K. and the Skypren (registered trademark) series manufactured by Tosoh Corp. When using these commercially available products, latex (a) made of a chloroprene homopolymer or latex (b) made of a chloroprene polymer having a carboxyl group in the molecule may be selected from the above commercially available products by appropriately referring to the above gel content and crystallization rate.
[0022] The self-adhesive pressure-sensitive adhesive composition of the present invention may further contain a tackifier resin in addition to the latex rubber, for example, chloroprene rubber latex (a) and (b) above). Examples of the tackifier resin include rosin resins such as gum rosin, tall rosin, wood rosin, disproportionated rosin, polymerized rosin, and other rosin ester resins such as glycerol esters and pentaerythritol esters of these rosins, and hydrogenated versions of these resins; terpene resins such as terpene resins, hydrocarbon-modified terpene resins, aromatic-modified terpene resins, and hydrogenated versions of these resins; terpene phenol resins such as terpene phenol resins and hydrogenated versions of terpene phenol resins; petroleum resins such as aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, copolymerized petroleum resins, dicyclopentadiene petroleum resins, pure monomer petroleum resins, and hydrogenated versions of these resins; styrene resins, coumarone-indene resins, alkylphenol resins, xylene resins, dammar, copal, and shellac. Considering the use of the present invention, chlorinated polyolefin resins that strengthen the adhesion to polyolefin resins are not usually used. In the self-adhesive adhesive composition according to the present invention, these tackifier resins are selected in consideration of, for example, compatibility with the latex rubber (chloroprene rubber latex) which is the elastomer component, not adversely affecting the gelation or crystallization of the latex, and not adversely affecting the initial tackiness or self-adhesiveness of the self-adhesive adhesive composition. As an example, a terpene phenol resin or a mixture of an aromatic modified terpene resin and a rosin ester resin can be used. These tackifier resins are preferably added in the form of an emulsion in order to disperse them uniformly in the self-adhesive adhesive composition. The tackifier resin can be blended in a ratio of, for example, 45 to 80 parts by mass with respect to a total of 100 parts by mass of the rubber latex (chloroprene rubber latex) calculated as a solid content.
[0023] In addition to the above-mentioned components, the self-adhesive adhesive composition of the present invention may contain other components, such as plasticizers / softeners, inorganic fillers such as calcium carbonate and silica, antioxidants, vulcanization accelerators, thickeners, surfactants, preservatives, defoamers, and dispersants.
[0024] The self-adhesive adhesive composition of the present invention is obtained by mixing the above-mentioned latex rubber (e.g., chloroprene rubber latex), a tackifier resin if desired, and other components if desired. Water may be added as necessary to adjust the concentration, and in that case, the solid content concentration of the self-adhesive adhesive composition can be about 10 to 50 mass%.
[0025] <Self-wearing products> The present invention relates to a substrate and a self-adhesive adhesive composition formed on at least one surface of the substrate. The present invention also covers a self-adhesive product having a self-adhesive adhesive layer formed on the substrate. The self-adhesive product preferably has the self-adhesive adhesive layer on both sides of the substrate. In the embodiment having the self-adhesive adhesive layer on both sides, the self-adhesive products are stacked on top of each other and the self-adhesive adhesive layers are bonded to each other, thereby suitably exhibiting the function of self-adhesion.
[0026] Examples of the substrate include a film, a nonwoven fabric, Japanese paper, a cotton fabric, a knitted fabric, a woven fabric, a laminated composite of a nonwoven fabric and a film, etc. Among these, from the viewpoints of breathability, stretchability, etc., a woven fabric, a knitted fabric, and a nonwoven fabric are preferred, and a woven fabric or a knitted fabric is more preferred. Examples of materials for these substrates include natural fibers such as cotton, silk, and linen; synthetic fibers such as polyester, polyamide, acrylic resin, polyurethane, polyethylene, and polypropylene; semi-synthetic fibers such as acetate fibers; and regenerated fibers such as rayon fibers and cupra fibers. Among these, woven fabrics made of cotton are preferred. To give elasticity to cotton woven fabrics, they can be partially replaced with elastic threads such as polyurethane threads. The appropriate number of elastic threads per inch in cotton woven fabrics is about 30 to 40 threads in the vertical direction and 15 to 80 threads in the horizontal direction. The basis weight of the woven fabric is usually 10 g / m 2 ~200g / m 2 It can be said that:
[0027] The self-adhesive adhesive composition is applied onto at least one surface (ie, one surface or both surfaces) of the substrate to form a self-adhesive adhesive layer. The coating amount of the self-adhesive adhesive layer can be appropriately selected depending on the properties of the substrate, the desired degree of self-adhesiveness, and the appearance and properties of the self-adhesive bandage, but is usually 5 to 100 g / m 2 , preferably 10 to 80 g / m 2 After the self-adhesive pressure-sensitive adhesive composition is applied, it is possible to obtain a self-adhesive product having a self-adhesive pressure-sensitive adhesive layer formed on at least one surface of a substrate by drying the composition.
[0028] [Self-adhesion force on the back] The self-adhesive strength of the self-adhesive product of the present invention can be evaluated by its back surface self-adhesive strength. In the present invention, the self-adhesive product, particularly a self-adhesive product in which a self-adhesive pressure-sensitive adhesive layer is formed on both sides of a substrate, can have a back-side self-adhesive strength in the range of, for example, 0.5 to 8.0 N / 38 mm, or 1.0 to 6.0 N / mm, or 1.5 to 5.0 N / 38 mm. By having the back-side self-adhesive strength within the above numerical range, the self-adhesive product can be a self-adhesive product that is difficult to peel off during use, but is easy to peel off when reapplied (rewound), making it possible to reapply (rewound). The back surface self-adhesive strength can be determined, for example, by cutting a self-adhesive product (a substrate having a self-adhesive adhesive layer coated and formed on both sides, the side on which the adhesive layer was formed first is called side I and the side on which the adhesive layer was formed second is called side II) into two pieces measuring 100 mm (lengthwise) x 38 mm (widthwise), attaching double-sided tape to stainless steel tape, attaching a test piece on top of the tape with side I facing down, and then attaching another test piece on top of the tape with side I facing down, and then pressing the pieces together twice with a 2 kg roller at 300 mm / min. 30 minutes after pressing, using an Instron tensile tester to measure the 180° peel strength (N) from the length direction at a speed of 300±30 mm / min (unit: N / 38 mm). It is desirable that the back surface self-adhesive strength does not decrease over time. For example, as described above, by making the self-adhesive adhesive of the present invention satisfy the melting endotherm specified in (1) and / or (2) after a predetermined period of time under predetermined conditions, and further satisfy the crystallinity specified in (3) and / or (4), it is possible to provide a self-adhesive product in which the decrease in the back surface self-adhesive strength from the initial manufacturing stage is suppressed. EXAMPLES
[0029] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0030] <Preparation of self-adhesive adhesive composition> Based on the blending amounts shown in Table 2, the self-adhesive pressure-sensitive adhesive compositions of Examples 1 to 4 were produced with a solid concentration of 30 mass % (concentration adjusted by ion exchange). The amount of each component in Table 2 is the mixing ratio (parts by mass, solid content equivalent) of other components (tackifier resin, other additives) when the total amount of CR Latex A and CR Latex B (solid content equivalent) is 100 parts by mass. The details of each component are shown in Table 1.
[0031] [Table 1]
[0032] <Self-adhesive adhesive composition: DSC measurement> For each of the self-adhesive pressure-sensitive adhesive compositions of Examples 1 to 4 above, a differential scanning calorimeter (DSC) measurement was carried out under the following storage and measurement conditions. (i) After storage for one month in an environment at 23°C, DSC measurement was performed under the following temperature increase and decrease conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, with a measurement temperature range of 0°C to 80°C, and in a nitrogen atmosphere. (ii) After storage for one month in an environment at 5°C, DSC measurement was performed under the following temperature increase and decrease conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, with a measurement temperature range of 0°C to 80°C, and in a nitrogen atmosphere. The melting endotherm of each sample was calculated from the obtained DSC curve. In addition, a differential scanning calorimeter (DSC) measurement was carried out under the above-mentioned conditions using only the CR latex rubber (mixing ratio: CR latex A:CR latex B = 60:40 (parts by mass)), and the ratio of the melting endotherm value of each sample to the obtained melting endotherm value, which was taken as 100%, was calculated as the crystallinity (%). The results are shown in Table 2.
[0033] <Preparation of self-adhesive product samples> Spray coating on both sides of a woven fabric base material (warp stretch fabric, warp threads: 40's cotton / polyurethane core spun yarn, 32±2 threads / inch, weft threads: 16's cotton, 72±4 / inch), with a total coating weight of approximately 40g / m2 on both sides after drying. 2 (One side: approx. 20g / m 2 The self-adhesive adhesive compositions of Examples 1 to 4 were applied so that the self-adhesive adhesive composition was applied to the first side and the second side was applied to the second side. The self-adhesive adhesive composition was then dried at 100°C for 3 minutes to produce a self-adhesive product sample having a self-adhesive adhesive surface on both sides.
[0034] For each of the obtained self-adhesive product samples, the back surface self-adhesive strength was measured immediately after production (initial stage), after storage at 23°C (1 month, 2 months, 3 months, 6 months), after storage at 40°C and 75% RH (1 month, 2 months, 3 months, 6 months), or after storage at 5°C (2 weeks, 1 month), and the stability of the samples at each storage temperature was evaluated. In the following description, the example numbers of the self-adhesive pressure sensitive adhesive compositions will also be treated as example numbers for evaluating the performance of self-adhesive product samples formed using the compositions.
[0035] <Measurement of self-adhesive strength (adhesive strength on the back side)> The back-side self-adhesive strength of the self-adhesive product samples was measured according to the 180-degree peeling method specified in JIS Z 0237. Specifically, from the self-adhesive product sample manufactured as above and stored under the specified conditions, two test pieces were cut into strips measuring 100 mm in length and 38 mm in width, and designated as test pieces 1 and 2. Double-sided tape was attached to a stainless steel tape, and test piece 1 was attached on top of it with its I-side facing down. Then, these were overlapped so that the II-side of test piece 1 and the I-side of the other test piece 2 faced each other. Next, a 2 kg rubber roll was pressed twice back and forth on the test piece 2 (side II) at a speed of 300 mm / min, leaving the end. Immediately after pressing and 30 minutes after pressing, the test piece 2 was peeled off from the test piece 1 at a peel angle of 180 degrees and a peel speed of 300 mm / min, and the 180°C peel strength (back surface self-adhesive strength, unit: N / 38 mm) of the test piece 2 against the test piece 1 was measured (average value of N=3). The measurement atmosphere was a temperature of 23±2°C and a relative humidity of 50±5%. If the back surface self-adhesive strength 30 minutes after application is 1.0 to 1.5 [N / 38 mm] or more, it can be evaluated that the overlapped portion will not peel off due to rubbing against the clothing worn, and the edge of the overlapped portion will not lift when the self-adhesive product is actually used. However, if the back surface self-adhesive strength exceeds 8 [N / 38 mm], rewinding (difficulty in unwinding the tape) becomes very heavy, the back surface becomes sticky, and this can lead to problems such as frictional peeling due to rubbing against clothing.
[0036] For samples stored at 23°C and 40°C, 75% RH, the rate of change in the back surface self-adhesive strength after storage for one month was calculated from that after storage for six months. For samples stored at 5°C, the rate of change in the back surface self-adhesive strength after storage for one month was calculated from the initial back surface self-adhesive strength (immediately after manufacture). Stability was evaluated according to the stability evaluation criteria below. Rate of change (%) = {[Back surface self-adhesive strength after 1 month (or initial) - Back surface self-adhesive strength after 6 months (or 1 month) storage] / Back surface self-adhesive strength after 1 month (or initial)} x 100 <Stability evaluation criteria> Rate of change (decrease) is less than 20% A Rate of change (decrease) is between 20% and 40%... B Rate of change (decrease) is 40% or more C * If the rate of change (%) is a positive value, it indicates that the back surface self-adhesive strength has decreased over time compared to the initial value (1 month after aging / or at the beginning), and if it is a negative value, it indicates that the back surface self-adhesive strength has improved over time compared to the initial value (1 month after aging / or at the beginning).
[0037] Table 3 shows the measurement results of the back surface self-adhesive strength under each condition and the results of the stability evaluation.
[0038] [Table 2]
[0039] [Table 3]
[0040] As shown in Tables 2 and 3, the self-adhesive adhesive compositions of Examples 1 and 2 were confirmed to be self-adhesive products with excellent stability over time, with the back-side self-adhesive strength evaluated as A in the self-adhesive products produced from the compositions after storage at 23°C for 6 months, storage at 40°C for 6 months at 75% RH, and storage at 5°C for 1 month. Note that the self-adhesive adhesives of Examples 1 and 2 had a melting endotherm of 0.5 J / g or less after storage at 23°C for 1 month, a melting endotherm of 0.1 J / g or less after storage at 5°C for 1 month, a crystallinity of 15% or less after storage at 23°C for 1 month, and a crystallinity of 5% or less after storage at 5°C for 1 month. In addition, Examples 1 and 2 use chloroprene rubber latex as the elastomer component, which not only accommodates the trend away from natural rubber latex, but has also been confirmed to have low adhesive stickiness and excellent initial tackiness, and to be a self-adhesive product that combines the low tackiness and high self-adhesive properties of previously proposed self-adhesive adhesives.
[0041] On the other hand, the self-adhesive adhesive compositions of Examples 3 and 4, which have a melting endotherm of 0.5 J / g or more after storage at 23°C for one month, a melting endotherm of 0.1 J / g or more after storage at 5°C for one month, and a crystallinity of 15% or more after storage at 23°C for one month, and a crystallinity of 5% or more after storage at 5°C for one month, were found to be unable to satisfy all of the stability evaluations of the back-surface self-adhesive strength under the above three storage conditions in the self-adhesive products made from these compositions. In addition, in Example 3, the amount of tackifier resin is smaller than in Examples 1 and 2, and in Example 4, a tackifier resin different from that in Examples 1 and 2 is used. It was confirmed that the melting endotherm, i.e., the crystallization of the CR latex, can be controlled by the selection and amount of the tackifier resin, which leads to the realization of the stability of the self-adhesive strength over time.
Claims
1. A self-adhesive pressure-sensitive adhesive composition containing latex rubber as an elastomer component, A self-adhesive pressure-sensitive adhesive composition that satisfies at least one of the following (1) and (2): (1) After storage for one month in an environment at 23°C, the self-adhesive pressure-sensitive adhesive composition has a melting endotherm of 0.5 J / g or less, as measured with a differential scanning calorimeter (DSC) (heating and cooling conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, measurement temperature range: 0°C to 80°C, in a nitrogen atmosphere). (2) After storage for one month in an environment at 5°C, the self-adhesive pressure-sensitive adhesive composition has a melting endotherm of 0.1 J / g or less, as measured with a differential scanning calorimeter (DSC) (heating and cooling conditions: 0°C → 100°C: 10°C / min, 100°C → 0°C: -10°C / min, measurement temperature range: 0°C to 80°C, in a nitrogen atmosphere).
2. The self-adhesive pressure-sensitive adhesive composition according to claim 1 , further satisfying at least one of the following (3) and (4): (3) After storage for one month in an environment at 23° C., the self-adhesive pressure-sensitive adhesive composition has a degree of crystallinity of 15% or less as measured by DSC. (4) After storage for one month in an environment at 5° C., the self-adhesive pressure-sensitive adhesive composition has a degree of crystallinity of 5% or less as measured by DSC.
3. The self-adhesive adhesive composition comprises a tackifier resin, The tackifier resin is a mixed resin of an aromatic modified terpene resin and a rosin ester resin, or a terpene phenol resin. The self-adhesive adhesive composition according to claim 1.
4. the latex rubber is a chloroprene rubber latex, The tackifier resin is contained in an amount of 45 to 80 parts by mass per 100 parts by mass of the chloroprene rubber latex in terms of solid content. The self-adhesive adhesive composition according to claim 3.
5. A self-adhesive product comprising a substrate and a self-adhesive layer formed from the self-adhesive adhesive composition according to any one of claims 1 to 4 on at least one surface of the substrate.
Citation Information
Patent Citations
Production of self-adhesive bandage
JP1988260553A
Self-adhesive bandage
JP1999089874A
Autohesive adhesive composition and autohesive product
JP2022168718A